Mechanisms and Robots Analysis with MATLAB® - Marghitu, Dan B. (Springer London : Imprint: Springer, 2009)
The knowledge of how to solve advanced dynamic concepts is vitally important in such areas as robotics, spacecraft, and multibody systems. Mechanisms and Robots Analysis with MATLAB® enables the reader to understand the mechanical behavior of complex engineering structures, mechanisms, and robots by discussing how to formulate the necessary mathematical equations and how to solve them using MATLAB®. This straightforward introduction to kinematics and dynamics using MATLAB® is complemented by a range of learning techniques that will benefit instructors, students, and researchers. The explanations of sample problems provide a model for student problem-solving through analytical and numerical techniques. By reading the theory and solving the accompanying problems the reader will acquire a solid working knowledge of basic theories in mechanics and in MATLAB®. Theory, computational aspects, and applications of mechanisms and robots are covered from both mathematical and physical perspectives, and topics are presented clearly and simply. This allows fundamental principles to emerge through applications solved with MATLAB® and emphasizes concepts, derivations, and interpretations of the general principles. Mechanisms and Robots Analysis with MATLAB® will allow students to build on their knowledge of mechanics and calculus to develop an interest in the classical principles of robotics and mechanism systems. Instructors will find this a useful teaching tool and even experts will be able to appreciate its clear, informative approach.